(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the outcome of Spinal Accessary nerve to Suprascapular nerve and motor branch of Radial nerve transfer to the Axillary nerve for restoration of shoulder abduction and external rotation in patients with C5-C6 brachial plexus injury. Methods: We conducted this descriptive study in National Orthopedics Hospital Bahawalpur. The study period extended from 12th June 2015 to 12th December 2020.All patients with C5-C6 injury fulfilling the inclusion criteria were operated with Spinal Accessary nerve to Suprascapular nerve and motor branch of Radial nerve transfer to the Axillary nerve. Post operative functional assessment was done by measuring shoulder abduction, external rotation and strength of abduction. Results: The total number of patients in this study were 14. Male patients were 13(92.85% ) and female 1(7.14%).The mean age was 29.2±7 years. Right shoulder was affected in 9(64.28%) patients and left in 5(35.7%). The mean follow up period was 24.2±3.3 months. The shoulder abduction improved from pre operative 0 o to 97.8o±4o while external rotation from 0 o to 30 o± 5o postoperatively. The abduction muscle strength as per Medical Research Council (MRC) scale was M4 in 9(64.28%) and M3 in 3(21.42%) patients. Conclusion: Satisfactory shoulder abduction with adequate muscle strength and external rotation was achieved in majority of our patients of C5-C6 brachial plexus injury treated with dual nerve transfer,This transfer utilized Spinal Accessary nerve to Suprascapular nerve and motor branch of Radial nerve to the Axillary nerve.